Pembelajaran Bahasa Arab berbasis Student-Centered Learning di Universitas KH. A. Wahab Hasbullah Jombang - M Dzikrul Hakim; Didin Sirojudin (Al-Lahjah, 2022)
This study aims to compare the student-centered learning (SCL) approach in higher education to the learning process in three different study programs, namely English Study Program, Islamic Religious Education and Arabic Language Education at KH. A. Wahab Hasbullah Jombang University . There are two main problems in this study, namely how the learning process is and what learning strategies are used in the three study programs. The method used in this study is a descriptive method with a qualitative approach. The results of this study indicate that the learning process for Arabic courses in English Study Program, Arabic courses in Islamic Studies Study Programs and Kalam Mukassaf courses in Arabic Education Study Programs has used the SCL approach, although the learning process of the three study programs used the strategy different. Learning strategies in Arabic courses in English Study Program use interactive learning strategies and guided teaching, Islamic Studies Study Programs in Arabic courses use interactive learning strategies, emphasizing discussion and sharing among students, while in education study programs Arabic in the Kalam Mukassaf course uses a peer lesson learning strategy, namely learning by teaching fellow friends.